ON BE PERFECT AS YOUR FATHER BASED ON MATTHEW 5:48 - Daniel Tulalessy; Gerry C.J. Takaria (Jurnal Koinonia, 2019)
In this survey, the author examines the understanding of the “perfect as yourfather” based on Matthew 5:48. The author focuses the research on Amboncongregation. The survey is based on three main indicators, namely:understanding of the word “perfect,” meaning of “be perfect as your father,” andhow to be perfect. Often there are people who don’t understand this so thatunderstanding and practice related to Jesus’ command in Matthew 5:48 is notgood.This study is divided into two parts, namely the study of the theory and fieldresearch. The results of theoretical research on be perfect as your Father isdivided into three parts, namely: First, the word “perfect” which is used inMatthew 5:48 can be translated to “spiritual matured” but it does not eliminatethe essence of the word perfect itself. Second, the meaning of be perfect as yourFather is used to explain that Father is the right standard so that we do not makestandards on others who might make us not grow because of the mistakes theymade. Third, the way to be perfect was explained by Jesus first in Matthew 5:3-11. Jesus explained spritual growth through 8 things, namely: spiritual poorcondition, mourning over the circumstances, preparing the heart for the HolySpirit, being hunry and thirsty for the word, having a change of character, themotive in all action is right, being a witness, and giving priority to God oneverything.The results of field research conducted through a questionnaire distributed toAmbon congregation which is divided into three indicators, namely:understanding of the word perfect, meaning of be perfect as your Father, andhow to be perfect. On each given indicators, the author found out that Amboncongregation have a very good understanding.